Epidemiologic and genetic aspects of spina bifida and other neural tube defects - Au, Kit Sing (2010)
The worldwide incidence of neural tube defects (NTDs) ranges from 1.0 to 10.0 per 1,000 births with almost equal frequencies between two major categories: anencephaly and spina bifida (SB). Epidemiological studies have provided valuable insight for (a) researchers to identify nongenetic and genetic factors contributing to etiology, (b) public health officials to design and implement policies to prevent NTD pregnancies, and (c) individuals to take precautions to reduce the chance of having an NTD-affected pregnancy. Despite extensive research, our knowledge of the genetic etiology of human NTDs is limited. Although more than 200 small animal models with NTDs exist, most of these models do not replicate the human disease phenotype. Over a hundred candidate genes have been examined for risk association to human SB. The candidate genes studied include those important in folic acid metabolism, glucose metabolism, retinoid metabolism, and apoptosis. Many genes that regulate transcription in early embryogenesis and maintain planar cell polarity have also been tested as candidates. Additionally, genes identified through mouse models of NTDs have been explored as candidates. We do not know how many genes in the human genome may confer risk for NTDs in human. Less than 20% of the studied candidate genes have been determined to confer even a minor effect on risk association. Many studies have provided conflicting conclusions due to limitations in study design that potentially affect the power of statistical analysis. Future directions such as genomewide association studies (GWAS) and whole exome or even whole genome sequencing are discussed as possible avenues to identify genes that affect risk for human NTDs.